2008
DOI: 10.1002/jcp.21378
|View full text |Cite
|
Sign up to set email alerts
|

L‐ and N‐current but not M‐current inhibition by M1 muscarinic receptors requires DAG lipase activity

Abstract: Stimulation of postsynaptic M(1) muscarinic receptors (M(1)Rs) increases firing rates of both sympathetic and central neurons that underlie increases in vasomotor tone, heart rate, and cognitive memory functioning. At the cellular level, M(1)R stimulation modulates currents through various voltage-gated ion channels, including KCNQ K+ channels (M-current) and both L- and N-type Ca2+ channels (L- and N-current) by a pertussis toxin-insensitive, slow signaling pathway. Depletion of phosphatidylinositol-4,5-bisph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 61 publications
2
17
0
Order By: Relevance
“…The DAGL ␣ cDNA 2-arachidonoylglycerol, has been implicated in the control of pain mechanisms ( 13 ) and cancer cell proliferation ( 14 ). DAGL enzymes have been found to be important in the production of 2-arachidonoylglycerol and in the control of appetite and pain ( 15 ) and also in the regulation of Ca 2+ infl ux into cells ( 16 ). We recently showed that 1-MAG is a coupling factor linking glucose metabolism to insulin secretion in pancreatic ␤ -cells and that ABHD6 specifi cally controls ␤ -cell 1-MAG levels ( 4 ).…”
Section: Sn -1-dagl Assaymentioning
confidence: 99%
“…The DAGL ␣ cDNA 2-arachidonoylglycerol, has been implicated in the control of pain mechanisms ( 13 ) and cancer cell proliferation ( 14 ). DAGL enzymes have been found to be important in the production of 2-arachidonoylglycerol and in the control of appetite and pain ( 15 ) and also in the regulation of Ca 2+ infl ux into cells ( 16 ). We recently showed that 1-MAG is a coupling factor linking glucose metabolism to insulin secretion in pancreatic ␤ -cells and that ABHD6 specifi cally controls ␤ -cell 1-MAG levels ( 4 ).…”
Section: Sn -1-dagl Assaymentioning
confidence: 99%
“…Voltage-independent inhibition is generally less well characterized and likely comprised of several distinct mechanisms including channel trafficking, phosphorylation and lipid signaling pathways (reviewed in ref. 34,35,40,[43][44][45][46][47][48]. The primary focus of this review is the direct, voltage-dependent inhibition of Ca V 2 channels.…”
Section: Subunits-functional Effectsmentioning
confidence: 99%
“…97 Likewise, truncating the N-terminal 55 amino acids of Ca V 2.2 prevented voltagedependent inhibition and introducing the Ca V 2.2 N-terminus into the Ca V 1.2 backbone conferred modest inhibition onto these normally resistant channels. 97,121 The N-terminus has a glycine rich stretch of amino acids (9-40) that is followed by eleven amino acids (45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55) that are predicted to form an α-helix.…”
Section: Structural Determinants On Gβγmentioning
confidence: 99%
“…Likewise, 2-AG can be oxygenated by a number of lipooxygenases to generate a ligand that can activate peroxisome-activated receptors [90]. There is also emerging evidence that DAGL-dependent pathways can inhibit L-and Ntype calcium currents [91], and regulate a form of synaptic plasticity mediated by a TRPV-like receptor [92]; however, it remains unclear whether these effects are mediated by 2-AG or by a 2-AG metabolite.…”
Section: Non-cannabinoid Functions For the Diacylglycerol Lipasesmentioning
confidence: 99%